Synthesis and Characterization of New Organosoluble and Thermally Stable Poly(thioether-amide)s Bearing Pyridine Subunit in the Main Chain. (27th April 2014) - Rostami, Esmael; Bagherzadeh, Maryam; Alinassab, Tahereh; Mohammadpour, Maryam; Zangooei, Masume; Feraidooni, Mahmood; Tavazo, Fatemeh; Keshavarz, Zahra
Abstract : We report the synthesis of new polyamides containing 2, 6-bis(2-thio-2-(4-carboxyphenyl)-1-oxo)pyridine subunit, under microwave irradiation using Yamasaki phosphorylation method. The solubility, thermal behavior, and viscosity of polyamides were evaluated. The structures of polymers have been characterized using IR and 1 H NMR spectroscopy. These polyamides showed good solubility, viscosity, high thermal stability, and glass transition temperatures. Their viscosities and glass transition temperatures are in the range of 0.63–0.88 and 223–295°C, respectively. Thermal stabilities for 10% weight loss (T10) are 137–173°C and for 50% weight loss (T50) are in the range of 483–523°C. The study of surface morphology showed particle and amorphous structures.